Pengaruh Social Media Marketing Instagram dan Brand Consciousness terhadap Brand Loyalty melalui Value Consciousness sebagai Variabel Intervening - Febrihana Rahma Sulistyani; Henny Welsa; Nonik Kusuma Ningrum (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine how much influence Social Media Marketing Instagram and Brand Consciousness have on Brand Loyalty through Value Consciousness as an Intervening Variable (Case Study at Starbucks in Yogyakarta City). The population used in this study are consumers who have purchased Stabucks products at least 2x. The sample in this study was 100 respondents using a quantitative approach, with purposive sampling technique. This data was taken using a questionnaire through the Google form, after the questionnaire results were collected, the data was tabulated using MS Excel and analyzed using multiple linear regression analysis using SPSS version 25. The results of this study indicate that Social Media Marketing has a positive and significant effect on Awareness Score. Brand Awareness has a positive and significant effect on Value Awareness. Value Awareness has no effect on Brand Loyalty. Social Media Marketing has a positive and significant effect on Brand Loyalty. Brand Awareness has a positive and significant effect on Brand Loyalty. The influence of Social Media Marketing on Brand Loyalty through Value Awareness as an intervening variable is rejected. The effect of Brand Awareness on Brand Loyalty through Value Awareness as an intervening variable is rejected.. Keywords : Social Media Marketing, Brand Consciousness, Value Consciousness, Brand Loyalty.